Vietnamese Feudal State with Anti-Corruption Work - Minh, Do Duc (VNU Journal of Science: Legal Studies; Vol 36 No 4, 2020)
Corruption is a “disease of power” that exists early in human society, since the division of power and establishment of social classes and states. It is an “abnormal behaviour of public servants for private benefits” - a “disease” of rulling force then corruption is a problem of states during historical process. In Vietnam, since feudal states, our fathers recognized harm of corruption and fought against it throguh many effective measures, among them, legislation is a main ones.